2004
DOI: 10.1128/jvi.78.17.9564-9567.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Central Half of Pit2 Is Not Required for Its Function as a Retroviral Receptor

Abstract: The type III sodium-dependent phosphate (NaP i ) cotransporter, Pit2, is a receptor for amphotropic murine leukemia virus (A-MuLV) and 10A1 MuLV. In order to determine what is sufficient for Pit2 receptor function, a deletion mutant lacking about the middle half of the protein was made. The mutant supported entry for both viruses, unequivocally narrowing down the identification of the sequence that is sufficient to specify the receptor functions of Pit2 to its N-terminal 182 amino acids and C-terminal 170 amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…In another study, deletion of about the middle half of human Pit2 was found to reduce A-MLV and 10A1 entry by 75% to 90% in CHO K1 cells compared to entry via wild-type human Pit2 (5). In this Pit2 mutant, the caveolin-binding consensus sequence in positions 226 to 233 is deleted.…”
Section: Discussionmentioning
confidence: 96%
“…In another study, deletion of about the middle half of human Pit2 was found to reduce A-MLV and 10A1 entry by 75% to 90% in CHO K1 cells compared to entry via wild-type human Pit2 (5). In this Pit2 mutant, the caveolin-binding consensus sequence in positions 226 to 233 is deleted.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, the plant protein is lacking the large intracellular loop present in animal PiTs. Furthermore, Bottger and Pedersen (9) showed that PiT2 retains its retroviral receptor function after deletion of loop 7 as well as transmembrane domains 6 -7 (pink shading in Fig. 5).…”
Section: Invited Reviewmentioning
confidence: 97%
“…To this aim, we constructed hPiT1 and hPiT2 chimeric proteins expressing the eYFP acceptor or Rluc donor. Since structure-function studies have excluded a role of the large intracellular loop (iLoop) in Pi transport and retrovirus binding (59)(60)(61)(62), and showed no overlapping between iLoop and the highly hydrophobic domain (57), we substituted the iLoop with eYFP and Rluc sequences ( Figure 3C). When expressed in HEK293T, the chimeric hPiT1-eYFP or -Rluc and hPiT2-eYFP or -Rluc proteins could be visualized at the plasma membrane, as shown by confocal microscopy ( Figure 3D), enabling to study their role in detecting the variation of extracellular Pi levels.…”
Section: Pit1 and Pit2 Form Hetero-oligomers Upon Variation Of Extracmentioning
confidence: 99%